Myocardial Infarctions and Other Acute Coronary Syndromes in Rare Congenital Bleeding Disorders: A Critical Analysis of All Reported Cases. (May 2015) - Girolami, Antonio; Ferrari, Silvia; Sambado, Luisa; Peroni, Edoardo; Cosi, Elisabetta
Objective: To investigate the occurrence of myocardial infarction or other acute coronary syndromes in rare congenital bleeding disorders. Patients: All patients with factor I (FI), factor II (FII), factor V (FV), factor VII (FVII), factor X (FX), factor XI (FXI), or factor XIII (FXIII) deficiency or abnormality reported to have presented a myocardial infarction or another acute coronary syndrome were investigated. The condition had to be demonstrated by objective means, including a coronary/angiography. Cases of stable angina were excluded. Results: A total of 53 patients (4 had FI, 2 had FV, 2 had FVII, 36 had FXI, 1 had FXIII deficiency, and 8 patients had platelet disorders) met the inclusion criteria . No patient with FII or FX deficiency and acute coronary disease met the inclusion criteria. In the majority of patients, common risk factors were present, namely hypertension, hypercholesterolemia, smoking, and diabetes. Replacement therapy was involved in 5 cases. Conclusion: The congenital hypocoagulability present in these patients was unable to allow a protection from acute coronary diseases. The significance of the findings is discussed.